Prevalence of Latent Tuberculosis among Hospital Administrative Staff in Kuala Lumpur - Mohd Hasni Jaafar; Kumaren Krishnan (Intelektual Pustaka Media Utama, 2016)
In the United States, there were about 10 to 15 million people with latent tuberculosis infection (LTBI) who are asymptomatic, particularly among healthcare workers (HCWs). The aim of the study was to determine the prevalence of LTBI among the HCWs in a main general hospital in Malaysia. About 401 HCWs have been enrolled in this cross sectional study conducted in November 2014 until January 2015. A standardised questionnaire was used to obtain their demography and job description together with Tuberculin skin test (TST). The prevalence of LTBI in the institution was about 46.4%, which was high. It was common amongst a younger age group and male HCWs. The noble finding was the study proved that the administrative type of work in a clinical setting has the highest prevalence and risk (adjusted OR=5.366; 95% CI=1.397-20.619) compared to others. Non-clinical HCWs like administrator should be treated as one of potential job for TBI in any hospital or clinic. Any programme on TBI awareness and prevention should include them too.